Validity and Reliability Indices for the Arabic Version of Purdue Perceptual – Motor Survey In Sultanat Oman - Hasan, Abdul-Hameed (Jordan Journal of Educational Sciences, 2007)
This study aimed at identifying the validity and reliability indices for the Arabic version of Purdue Perceptual – Motor Scale, which was prepared originally by Newell Kephert and Eugene Roach in accordance with Kephert concept. This concept is included in Kephert’s theory of perceptual motor abilities. The scale consisted of 31 items representing 11 subtests distributed on 5 different fields: (balance, posture, body image, perceptual motor match, ocular control and form perception). To find the validity and reliability of the scale, It was applied on a convenience sample which consisted of 144 male and female students. Seventy- two of the total sample were high achievers (42 boys and 30 girls) and seventy- two had learning disabilities (42 boys and 30 girls). Subjects were selected from the second and third grades of the basic educational phase in Muscat educational district. The content, predictive, and construct validity was achieved. The reliability of the test was calculated by Test-Retest and Cronbach alpha. Derived standard T-Score were derieved too. The result of the study showed that the validity and reliability values were high and significant.